Feasibility and outcomes from an integrated bridge treatment program for opioid use disorder - James R. Langabeer; Tiffany Champagne‐Langabeer; Andrea J. Yatsco; Meredith M. O'Neal; Marylou Cardenas‐Turanzas; Samuel Prater; Samuel Luber; Angela Stotts; Tom Fadial; Gina Khraish; Henry Wang; Bentley J. Bobrow; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objective With a significant proportion of individuals with opioid use disorder not currently receiving treatment, it is critical to find novel ways to engage and retain patients in treatment. Our objective is to describe the feasibility and preliminary outcomes of a program that used emergency physicians to initiate a bridge treatment, followed by peer support services, behavioral counseling, and ongoing treatment and follow‐up. Methods We developed a program called the Houston Emergency Opioid Engagement System (HEROES) that provides rapid access to board‐certified emergency physicians for initiation of buprenorphine, plus at least 1 behavioral counseling session and 4 weekly peer support sessions over the course of 30 days. Follow‐ups were conducted by phone and in person to obtain patient‐reported outcomes. Primary outcomes included percentage of patients who completed the 30‐day program and the percentage for successful linkage to more permanent ongoing treatment after the initial program. Results There were 324 participants who initiated treatment on buprenorphine from April 2018 to July 2019, with an average age of 36 (±9.6 years) and 52% of participants were males. At 30 days, 293/324 (90.43%) completed the program, and 203 of these (63%) were successfully connected to a subsequent community addiction medicine physician. There was a significant improvement (36%) in health‐related quality of life. Conclusion Lack of insurance is a predictor for treatment failure. Implementation of a multipronged treatment program is feasible and was associated with positive patient‐reported outcomes. This approach holds promise as a strategy for engaging and retaining patients in treatment.